Cardiovascular risk in active, insufficiently active and inactive users of public parks - Taís Tinucci; Teresa Bartholomeu; Gustavo Fernades de Oliveira; Cláudia Lúcia de Moraes Forjaz (Universidade Federal de Santa Catarina, 2008)
Physical activity has been recommended for heart disease prevention and rehabilitation. However, when performed incorrectly, which is more common when practiced without supervision and in public places, the risk of cardiovascular events increases. The objective of this study was to compare cardiovascular risk factors among users of São Paulo´s public parks with differing levels of physical activity - active, insuffi ciently active, and inactive. The evaluation consisted of a questionnaire about cardiovascular diseases, symptoms and risk factors; physical activity practice; and anthropometric and arterial blood pressure measurements. There was no difference between the groups in terms of the prevalence of cardiovascular disease or controllable risk factors. However, inactive people had a higher prevalence of cardiovascular symptoms (35%). With regard to uncontrollable cardiovascular risk factors, there was a higher prevalence of the gender/age factor among active (50%) and insuffi ciently active (45%) subjects, and heredity was more prevalent among inactive people (35%). There was no difference in obesity or blood pressure between the groups. The study also showed that active and insuffi ciently active subjects have a better knowledge of their health status, and a higher prevalence of being prescribed physical activity by physicians. The results demonstrate that most of the people who exercise in public parks are elderly and are at a moderate to high cardiovascular risk from this practice, which suggests that a physical education professional should be present. Resumo A prática de atividades físicas tem sido recomendada para a prevenção e reabilitação cardíacas. Porém, quando feita de maneira inadequada, o que ocorre mais freqüentemente na ausência de supervisão em locais públicos, esta prática pode se associar ao aumento do risco de acometimentos cardiovasculares. Comparar o risco cardiovascular de freqüentadores de parques públicos de São Paulo com diferentes níveis de prática de atividade física - ativos, insuficientemente ativos e inativos. Métodos: A avaliação constou de questionário sobre a presença de doenças, sintomas e fatores de risco cardiovasculares e sobre a prática de atividade física, além de medidas antropométricas e da pressão arterial. Não houve diferença significante na prevalência de doenças e fatores de risco controláveis entre os grupos. Porém, os inativos apresentaram maior prevalência de sintomas cardiovasculares (34%). Quanto aos fatores não-controláveis, a prevalência do fator sexo/idade foi maior nos ativos (50%) e insuficientemente ativo (45%), e a hereditariedade foi mais observada nos inativos (35%). Além disso, não foram observadas diferenças entre os grupos nas medidas de obesidade e pressão arterial. Por fim, observou-se que os ativos e insuficientemente ativos têm maior conhecimento sobre sua saúde e possuem mais recomendação médica para a prática de atividade física. Esses dados indicam que grande parte dos praticantes de atividades físicas nos parques é formada por idosos e apresenta risco cardiovascular moderado a alto para esta prática, o que levanta a importância da presença de um profissional da área de atividade física nesses locais.